Enhancing Trade Secret Protection amidst E-commerce Advancements: Navigating the Cybersecurity Conundrum - Hari Sutra Disemadi; Henry Soelistyo Budi (Sekolah Tinggi Hukum Bandung, 2023)
The e-commerce ecosystem has encompassed various aspects of life, giving rise to legal implications, particularly in the areas of intellectual property and personal data protection, which are now inseparable from Indonesia’s economic system in the digital age. This research aims to elucidate the legal relationship between trade secrets as a crucial form of intellectual property to be safeguarded in the digital era and analyze Indonesia’s legal capability to protect trade secrets amidst the escalating challenges of cybersecurity due to the widespread use of various forms of e-commerce. The research employs a normative legal research method to analyze the protection and legal certainty concerning trade secrets, which can be subject to unauthorized access or theft through cyberattacks. Utilizing a legislative approach, the research relies on secondary data in the form of primary legal sources. The findings of this research reveal political-legal issues and normative shortcomings in regulating e-commerce and trade secrets, often underestimating the digital threats that can harm individuals’ intellectual property rights.